A new species of Pristimantis Jimnez de la Espada, 1870 (Anura: Strabomantidae) from the Brejos de Altitude in Northeast Brazil - Roberto, Igor Joventino; Loebmann, Daniel; Lyra, Mariana L.; Haddad, Cliof B.; Vila, Robson Waldemar (Magnolia Press, 2022)
Pristimantis is the most diverse Neotropical genus of terrestrial vertebrates and is distributed from Central America to Argentina. The last few years have seen the description of several new species of the genus, suggesting that its diversity is still underestimated. After decades of uncertainties about the taxonomic status of populations of Pristimantis from the Brejos de Altitude of the state of Cear, Northeast Brazil, we finally found morphological, acoustic and molecular evidence confirming their distinctiveness from other Atlantic Forest species. The new species is characterized by the following: shagreen dorsal skin with small-scattered tubercles, absence of dorsolateral fold, presence of tarsal fold, advertisement call composed of 18 pulsed notes, (25 pulses per note), and dominant frequency located in the second energy band, ranging from 36174220 Hz. Phylogenetic analysis placed the new species in the Pristimantis conspicillatus species group and the sister lineage of the Atlantic Forest clade comprising P. ramagii, P. paulodutrai and the P. vinhai species complex.